The economics of natural resources - Rodríguez Carbajal, Genaro Armando (2024)
The book “The Economics of Natural Resources”, edited by the Research Center of the Universidad del Pacífico and written by Elsa Galarza Contreras, acquires notable relevance in the context of the current global emergency in the face of climate change (including events such as extreme temperatures) and the responses of countries and international organizations in this regard. The content of the book stands out for its interest in linking natural resources with the economy, incorporating the fundamentals of environmental science. The author supports her analysis in each chapter, addressing sensitive issues such as nature, ecology, population, externalities, rent, taxes, bioeconomic balance, social efficiency, concessions, property rights, private and state disposition, as well as the role of governments, energizing the agenda through remediation, safeguarding and the search for sustainable solutions to environmental problems linked to natural resources.